The Impact of Government Investment Spending and Inflation on Private Investment in Saudi Arabia - Almosabbeh, Imadeddin (Jordan Journal of Economic Sciences, 2020)
The aim of this study is to investigate the nature of the impact of government investment spending and inflation on private investment spending in Saudi Arabia during the period of (1970-2015). The study used the Saudi Arabian Monetary Authority and PWT 9.1data sets. The study used the NARDL method of Shin and Greenwood (2014). The results showed that the relationship between inflation and private investment spending is symmetry, while it is asymmetric in the case of government investment expenditure. The increase in government investment does not affect private investment, while the decline in government investment leads to a decline in private investment at a high rate.